SOSIALISASI INGAT PESAN IBU 3 M DI PANTAI RINDU ALAM KABUPATEN TANAH BUMBU - Nur Mahdi; Deni Setiawan; Andi Sultang AS; Nur Meina Anjeli; Nur Rahmi; Wilda Maulida Nur Fatimatuzzahra (Jurnal Bakti untuk Negeri, 2022)
Compliance with implementing health protocols continues to decrease in the Pandemic era that is not over. Data on COVID-19 sufferers as of July 2021 shows a significant increase from the previous day in both active cases and death cases. The distribution of close contact rates increases significantly. This allows COVID-19 transmission to improve a massive in a few months. This service activity is to increase public knowledge about the disease and the prevention of Covid-19 diseases accompanied by education and the distribution of masks aimed at helping the community increase compliance to participate in preventing COVID-19 transmission actively. The socialization method remembers the message of this 3 M mother with the distribution of leaflets and masks accompanied by education to visitors. Before and after education, visitors are given a pre-post test sheet to measure visitors understanding. The pre-test average knowledge/ ability of participants was 49.9%, and at the end of the session, there was an increase indicated by the post-test result of 58.32%.